Worldwide prevalence of hypospadias. Issue 3 (June 2016) - Springer, A.; van den Heijkant, M.; Baumann, S.
Summary: Introduction: Hypospadias is a common congenital malformation. Surgical repair and management of the long-term consequences require a substantial amount of socioeconomic resources. It is generally accepted that genetic and environmental factors play a major role in the etiology of hypospadias. There have been contradictory reports on rising hypospadias rates, and regional and ethnical differences. The exact prevalence of hypospadias is of major interest for healthcare providers, clinical medicine, and research. Objective: To review the literature regarding the worldwide prevalence of hypospadias. Study design: Pubmed, EMBASE and Google were systematically screened for: hypospadias, congenital malformation, anomaly, incidence, prevalence, and epidemiology. Exclusion criteria were surgical and risk-factor studies. To give an additional comprehensive overview, prevalence data were harvested from the Annual Report of the International Clearinghouse Centre for Birth Defects Surveillance and Research. Prevalence was reported as per 10, 000 live births. Results: Data were available from 1910 to 2013. The median study period was 9 years (range: 1–36 years). Approximately 90, 255, 200 births have been screened in all studies. The mean prevalence were: Europe 19.9 (range: 1–464), North America 34.2 (6–129.8), South America 5.2 (2.8–110), Asia 0.6–69, Africa 5.9 (1.9–110), and Australia 17.1–34.8. There were major geographical, regional, and ethnical differences, with an extreme heterogeneity of published studies. Numerous studies showed an increasing prevalence; on the other hand, there were a lot of contradictory data on the prevalence of hypospadias. The summary table shows contradictory data from the five largest international studies available. Discussion: There was huge literature available on the prevalence of hypospadias. Most data derived from Europe and North America. Many methodological factors influenced the calculation of an accurate prevalence, and even more of the true changes in prevalence over time (no generally accepted and standardized definition of hypospadias, different monitoring systems, unclear efficiency of notification and data ascertainment, etc.). There was wide variation of prevalence according to countries and ethnicity, and there were conflicting data on the recent trends of prevalence. Moreover, there weren't any epidemiologic data available from many parts of the world. Conclusion: True prevalence of hypospadias and trends were difficult to estimate. For the future, to be able to assess the true prevalence of hypospadias and changes in prevalence collaboration of national and international prospective registers is recommended. Study Year Country Per 10, 000 live births Time period Trend Bergman et al. 2015 23 European regions 18.6 2001–2010 Different trends Chul Kim et al. 2011 South Korea 1.4–3.3 2000–2004 Increasing Elliott et al. 2011 USA 42 1985–2006 No increase Paulozzi 1999 International registries 10–45 1964–1997 Partial increase Paulozzi et al. 1997 USA 17–50 1968–1993 Increasing 1970–1993